Beyond a Professional Association: IMLA Indonesia in the Transformation of Arabic Education in Indonesian Higher Education - Syarifaturrahmatullah Syarif; Uril Bahruddin; Sutaman; Muhammad Yamin; Mahbub Humaidi Aziz (UIN Syekh Wasil Kediri, Indonesia, 2026)
Arabic language education in Indonesia has undergone substantial transformation over the past two decades, as reflected in curriculum reforms, the expansion of undergraduate and graduate programs, and the growing volume of scholarly publications and academic networks. However, previous studies have predominantly focused on pedagogical aspects, while the role of professional associations as agents of educational transformation has received comparatively limited scholarly attention. This study aims to examine the contribution of the Indonesian Ittihadu al-Mudarris al-Lughah al-'Arabiyyah (IMLA) to the transformation of Arabic language education in higher education institutions. Employing a qualitative historical approach through the perspective of oral history, the study draws on in-depth interviews with twelve key informants representing different leadership periods of IMLA, complemented by organizational documents. The data were analyzed using qualitative content analysis based on the framework proposed by Graneheim and Lundman. The findings reveal that IMLA has evolved beyond the conventional functions of a professional association by performing three interconnected roles: as an epistemic community, a professional association and platform for academic consolidation, and a driving force behind the transformation of Arabic language education. The study further demonstrates that the transformation of Arabic language education has been shaped not only by pedagogical reforms and educational policies but also by the interaction between knowledge production, collective agency, and educational structures. These findings highlight the complementary explanatory power of Epistemic Community Theory and Structuration Theory in demonstrating how a professional association can transcend its representative function to become a catalyst for the transformation of Arabic language education in Indonesian higher education.